Plastic waste management in Malaysia: Current status, key challenges and opportunities - Md Ali, Umi Fazara; Ahmad, Nor Ashikin; Shuaib, Norshah Aizat; Mohamed Sultan, Al Amin (Lembaga Jurutera Malaysia, 2020)
Plastics are essential in daily life, providing societal benefits such as safe food storage, health improvements, clean energy growth, and transportation. Since 1950, global production of plastic materials has increased, with over 340 million tonnes produced annually. Common plastics like polyethylene, polypropylene, and polystyrene are made from hydrocarbon monomers, with elements like oxygen, chlorine, fluorine, and nitrogen. Degrading these materials takes 15 to 10,000 years, and if mismanaged, it ends up in landfills, beaches, rivers, and oceans, contributing to environmental problems. Plastics have the smallest recycling rate globally, with only 9% recycled, 12% burned, and 79% ending up in landfills or the natural environment.